Compendium on the Legal Protection of Human Rights Defenders in Africa (Pretoria University Law Press (PULP), 2018)
This compilation of documents has been prepared by the Special Rapporteur on Human Rights Defenders and Focal Point on Reprisals in Africa of the African Commission on Human and Peoples' Rights, Commissioner Rémy Ngoy Lumbu, with the assistance of the Centre for Human Rights, Faculty of Law, University of Pretoria. The aim of this compilation is to bring together all the most relevant documents concerning the protection of human rights defenders in Africa, adopted under the auspices of the United Nations, the Council of Europe, the European Union, the OSCE and the African Union. This publication, which appears for the first time in 2018, is timely for two particular reasons: The year 2018 marks 20 years since the adoption by the UN General Assembly of the Declaration on Human Rights Defenders. In 2018, human rights across the world, and in Africa, have increasingly made the target of government attack and recrimination.